Improving battery safety and sustainability through testing material advances and industry developments - Zoltan Weltsch; Tibor Cseke; Robert Kun (Discover Sustainability)
Abstract The transition to renewable energy is essential for sustainable development, in which advanced energy-efficient storage solutions, in particular rechargeable batteries, play a key role. Batteries are becoming increasingly important not only for electric mobility and grid balancing, but also for industrial and residential applications. However, as energy density increases, so do safety risks such as thermal runaway, which can jeopardise user confidence. The aim of this study is to examine the battery technology value chain at a systemic level, with a particular focus on the role of safety testing and technological innovation. The research identifies three main gaps in literature: the lack of value chain level integration, the under-representation of AI-based safety technologies, and the limited comparison of regional (EU, US, Asia) regulatory regimes. By examining the interrelationships between material selection (cathode, anode), cell design, testing protocols and regulatory environment, the study highlights the complex challenges and development directions for battery energy storage. The study reviewed global industry trends and critically assessed forecasts and analyses from international consultancies such as Ernst & Young (EY). These concluded that thorough testing of lithium-ion batteries is key to ensuring long-term reliability, safety and performance by reducing operational risks and increasing product efficiency. Advanced testing infrastructure not only serves quality control and regulatory compliance, but also makes a fundamental contribution to increasing energy efficiency and supporting the green transition. For Europe in particular, it is of paramount importance to expand testing capacities to enable the continent to take a leading role in the safe and sustainable development of batteries.